Analysis of Community Structure in Essential Ecosystem Zones - Akbar, Muhammad Firmansyah; Idris, Muhammad Husni; Anwar, Hairil (Jurnal Biologi Tropis, 2024)
Mangrove forest plant communities living in coastal areas have a significant influence on people’s lives ecologically  and economically. As well as cultivating fisheries commodities and protecting coastal areas from abrasion and stroms, mangrove areas also play an important role in climat change issues. Due to their importance, some water and wetland areas with high conservation value are designated as Essential Ecosystem Areas. Lembar and Sekotong Bay is one of them. This study aims to observe the condition of plant structure and composition in essential areas as well as the environmental conditions that support plant growth. To do this, indices of density, relative density, frequency, relative frequency, dominance, and importance value index were taken from each mangrove species. This was done through vegetation analysis. The observation site consisted of six stations, each of which had 78 observation plot point. The results showed that there were seven mangrove species in the ecosystem area of importance: Rhizophora Apiculata, Rhizophora Stylosa, Rhizophora Mucronata, Bruguira Gymnorrhiza, Avicennia Marina, and Excoaria Agallocha. The highes species density and relative density were owned by Rhizophora Stylosa, and the lowest relative density was owned by Excoaria Agallocha. The Highest species frequency and relative frequency are own by Rhizophora Stylosa Overall, the condition of important mangrove area is still in the medium-dense category. Environmental factors such as temperature, saline, pH, and Humidity are very helpful for the growth of mangrove species.